2011
DOI: 10.3109/08916934.2011.571223
|View full text |Cite
|
Sign up to set email alerts
|

Oral GABA treatment downregulates inflammatory responses in a mouse model of rheumatoid arthritis

Abstract: Current treatments for rheumatoid arthritis (RA) have long-term side effects such that new treatments are needed that can safely help manage the disease. There is a growing appreciation that GABA receptors (GABA-Rs) on immune cells provide new targets that can be used to modulate immune cell activity. Here, we show for the first time that activation of peripheral GABA-Rs can inhibit the development of disease in the collagen-induced arthritis (CIA) mouse model of RA. Mice that received oral GABA had a reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(121 citation statements)
references
References 21 publications
5
113
0
3
Order By: Relevance
“…Tian et al [61] showed that activation of peripheral GABA receptors ameliorates this disease in mice. The T cells of mice treated with GABA displayed reduced proliferative responses to collagen, and their APCs reduced stimulatory capacity.…”
Section: Collagen-induced Arthritis (Cia)mentioning
confidence: 98%
“…Tian et al [61] showed that activation of peripheral GABA receptors ameliorates this disease in mice. The T cells of mice treated with GABA displayed reduced proliferative responses to collagen, and their APCs reduced stimulatory capacity.…”
Section: Collagen-induced Arthritis (Cia)mentioning
confidence: 98%
“…When GABA opens the GABA-A channels in the immune cells' plasma membrane, the membrane potential will change and can thereby affect a number of cellular processes including the entry of calcium into the cell by decreasing the driving force on the calcium ion ( Fig. 5.2 (Bhat and Steinman 2009;Mendu et al 2011;Soltani et al 2011;Tian et al 2011;Wheeler et al 2011). Neuroinflammation is also involved in epileptogenic processes in the brain (for review see Vezzani et al 2008) where infiltration of leukocytes into the brain (Fabene et al 2008;Zattoni et al 2011) and increased production of pro-inflammatory cytokines (Li et al 2011) have been shown to be associated with the induction and progression of epilepsy.…”
Section: Resultsmentioning
confidence: 99%
“…GABA is decreased in serum of MS patients (Demakova et al 2003), oral GABA treatment downregulates inflammatory responses in a mouse model of rheumatoid arthritis (Tian et al 2011), disregulation of GABA metabolism precedes pancreatic islets autoimmunity in children who later progress to type 1 diabetes (Oresic et al 2008) and GAD is a major autoantibody in type 1 diabetes (Lernmark et al 1978). What role the GABA system has in these diseases remains nevertheless to be clarified.…”
Section: Gaba In Immune and Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…GABA acts on GABA receptors to affect a variety functional properties of the immune cells, such as cytokine secretion, cell proliferation, phagocytic activity and chemotaxis [10,11]. Increasing GABAergic activity ameliorates the progression of autoimmune diseases, such as multiple sclerosis, diabetes mellitus and rheumatoid arthritis [12,13,14,15]. …”
Section: Introductionmentioning
confidence: 99%